COMPANY RESPONSIBILITY FOR DAMAGE TO COMMUNITY AGRICULTURAL LAND RESULTING FROM INDICATED GAS LEAKAGE IN ROBURAN DOLOK VILLAGE FROM THE MAQASHID SYARIAH PERSPECTIVE - Ishaq London Lubis; Rahmad Efendi (Program Pascasarjana UIN Sumatera Utara, 2026)
This study aims to analyze the legal liability of PT Sorik Marapi Geothermal Power (SMGP) for the damage to agricultural land and environmental impacts that occurred in Roburan Dolok Village, Mandailing Natal Regency, and to review it from the perspective of Maqashid Syariah. The background of this study departs from a series of incidents of hydrogen sulfide (H₂S) gas leaks and hot mudflows that are strongly suspected to be related to the company's operational activities, which not only caused casualties, but also damaged dozens of agricultural areas and threatened the sustainability of the livelihoods of agrarian communities. This condition raises legal and ethical problems related to the enforcement of corporate liability in high-risk business activities. The focus of the research problem is directed at the application of the strict liability doctrine as regulated in Article 88 of Law Number 32 of 2009 concerning Environmental Protection and Management, and its relevance to the principles of Maqashid Syariah, especially the protection of life (hifz al-nafs), protection of property (hifz al-mal), and protection of the environment (hifz al-bi'ah). The research method used is normative legal research with a descriptive-analytical approach. The research data is sourced from primary legal materials in the form of relevant laws and regulations, as well as secondary legal materials in the form of scientific literature and credible media reports that document the facts of environmental damage and its impact on society. The analysis was conducted by examining positive legal norms and integrating them with the Maqashid Syariah approach as an ethical-normative framework. This research is expected to provide theoretical contributions to the development of Islamic environmental law and serve as a practical reference for enforcing just and welfare-oriented corporate accountability.